STRATEGIES TO STRENGTHEN THE AFFECTIVE DOMAIN IN LEARNING PANCASILA AND CITIZENSHIP EDUCATION FOR CLASS XII STUDENTS OF MAN 4 PANDEGLANG - Uus Fujiana; Damanhuri; Wika Hardika Legiani (Journal Civics And Social Studies, 2022)
This research aims to determine strategies for strengthening the affective domain in PPKn learning for class XII students and to determine the inhibiting and supporting factors in implementing strategies for strengthening the affective domain in PPKn learning for class This research uses a qualitative approach with descriptive methods. The results found are, strategies for strengthening the affective domain of students using learning models and methods that aim to improve the affective domain of students for the better, such as habituation models in the form of assignment methods and monitoring good student attitudes and behavior, exemplary models in the form methods of displaying good attitudes and behavior. The strategy to strengthen the affective domain can work well and students can follow and are able to achieve the goal of strengthening the affective domain. Then the way to overcome the obstacles experienced in implementing strategies to strengthen the affective domain in PPKn learning is to use a personal approach method to students, especially students whose affective domain or attitude is lacking and also students who are felt to be experiencing difficulties in learning.